Desenvolvimento de hidromel e estudo da sua maturação utilizando chips de carvalho (Quercus spp.) em diferentes níveis de tosta - Fortes, Juciane Prois (2023)
The search for new fermented beverages has put mead in evidence in recent decades, increasing its production and consumption, thus increasing its economic relevance and offering small honey producers an alternative to obtain a honey derivative with high added value. Currently, manufacturers of this drink are looking for ways to diversify production by introducing new aromas and flavors as a way to improve the sensory and physical-chemical quality, bringing differentiated products to the market. In view of this, the objective of this work was to develop a mead with honey from different floral origins and to evaluate the potential of using oak chips (Quercus sp.) at different levels of toasting in the maturation process. In the first experiment, meads produced from multifloral honey, orange blossom honey and their mixture in a 50/50 ratio were analyzed. The physical-chemical composition, the phenolic compounds generated by LC-ESI-QTOF-MS/MS and acceptance through sensory analysis were analyzed. The total phenolic compounds of multifloral and orange blossom honey were 485.84 and 471.31 mg GAE L1 , respectively, while meads ranged from 203.40 to 223.83 mg GAE L -1 . Antioxidant activity was 1.94 and 1.20 mM TEAC L-1 for honeys and 1.80 to 2.16 mM TEAC L-1 for meads. The phenolic compounds identified in the meads were chlorogenic, protocatechuic, syringic, pcoumaric acid and flavonoids naringenin and quercetin. Sensory analysis showed no difference regarding preference. From these results it was possible to define the use of multifloral honey as the main source for the second experiment, where the mead was matured with oak chips (Quercus sp.). The second experiment resulted in the published article “Enhancement of the functional properties of mead aged with oak (Quercus) chips at different toasting levels”. The results found in mead with the addition of oak chips showed an increase in the variability of phenolic compounds, flavonoid content and antioxidant capacity over the maturation time, regardless of the toast used, there was an increase in the functional quality of the drink. Compounds belonging to the classes of organic acids, phenolic acids, flavonoids and tannins were identified by LC-ESI-MS/MS in meads after 360 days. Meads with added oak chips are richer in phenolic compounds than base mead (honey only). Finally, the results of this scientific production show that mead is a beverage that carries the compounds present in honey and that the addition of oak chips (Quercus sp.) in its maturation process can be a promising tool to increase phenolic compounds and the quality of the meads.